23 LIPOSOMAL CURCUMIN REDUCES GROWTH IN HEAD AND NECK SQUAMOUS CELL CARCINOMA CELL LINES. Issue 1 (1st January 2007) - Tang, C. G.; Ho, B.; Wang, D.; Veena, M. S.; Ahmed, S.; Srivatsan, E. S.; Wang, M. B.
Abstract : Squamous cell carcinoma of the head and neck (HNSCC) represents 5% of cancers diagnosed annually in the United States. Five-year survival rates for advanced head and neck cancer have not improved significantly in the last 30 years. The significant morbidity associated with current treatments has led to continuing investigation of potential alternative and less toxic therapies. One such therapeutic agent, curcumin, has been shown to reduce tumor volume both in vitro and in vivo, but studies also have shown that absorption of curcumin is poor. In this study, we developed a new modality of delivering curcumin, via liposomes, that is less toxic and has increased absorption. This study compares the toxicity and effectiveness of curcumin delivery by DMSO (dimethylsulfoxide) versus liposomes in two aggressive oral cancer cell lines: SCC-1 and CAL-27. After 24 hours of growth followed by 24 hours of serum starvation, the tumor cells were treated with DMSO, DMSO + curcumin, liposomes, or liposomal curcumin at concentrations of 0, 50, 100, 200, 400, or 600 μM for 8 hours. After treatment, cells were allowed to grow additionally for 12 or 36 hours without any treatment. Media was then removed, and an MTT assay was performed by measuring OD at 570 nm. Results show that liposomes are significantly less toxic than DMSO in both cells lines ( p value = 0.0125 with a two-sample unequal variance t -test). Growth inhibition by liposomal curcumin is similar to that achieved with curcumin dissolved in DMSO and was similar for cells grown for 12 or 36 hours after treatment. These results suggest that liposomal curcumin is a more efficacious way of delivering curcumin to target cells. Since liposomes are taken in by membrane encapsulation, it is anticipated that curcumin absorption will also increase in vivo. We feel that liposomal delivery of curcumin will be valuable as a potential novel chemotherapeutic agent for the inhibition of head and neck tumor growth in animal models. Promising data from studies of in vivo models would lend support for testing liposomal curcumin in a phase 1, dose-escalation and safety trial in patients with HNSCC.